Psychological features of the relationship between hardiness and self-esteem in difficult life situations - DANYLIUK, Ivan; PREDKO, Viktoria; KYSLYNSKA, Anzhelika (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The article reveals the psychological relationship between hardiness and self-esteem. It is emphasized that hardiness is a pattern of internal attitudes of a personality, which is the basis of courage and bravery, a kind of belief system of a person that gives him or her a sense of self-confidence and provides an opportunity to rely on their own strength in difficult periods of life. At the same time, it is emphasized that a favorable self-esteem is a necessary factor in overcoming difficulties and stressful circumstances. Objective: to reveal the psychological features of the relationship between self-esteem and personality hardiness. To identify the main factors of self-esteem.Methods. The study involved 135 people, including 34 men and 101 women. Three methods were used: "S. Maddi's Hardiness Survey (adapted by D. Leontiev); S. Kovalev's Self-Esteem Test Questionnaire; J. Crocker's Contingencies of Self-Worth (adapted by O. Molchanova and T. Nekrasova). The study used methods of quantitative data processing, methods of statistical data analysis: Pearson correlation coefficient, ANOVA model (regression analysis).Results. It was found that the vast majority of respondents have low self-esteem, which is accompanied by sensitivity to criticism, excessive shyness, and a tendency to adapt to others. It was found that the overall level of self-esteem of women is higher than that of men. However, among the peculiarities of self-esteem manifestation, men showed a higher level of such self-esteem indicators as "Family Support", "Rivalry with Others", "Approval of Others" and "Love", while women showed a higher level of "Morality". The article also reveals a strong direct correlation between hardiness and self-esteem. Also, a direct correlation was found between hardiness and such self-esteem indicators as family support, morality, approval of others; appearance and love (interpersonal relationships). A regression model was built, which allowed us to identify the main predictors of self-esteem, including: approval of others, morality, competitiveness and involvement.Conclusions. There is a strong commection between hardiness and self-esteem, which provides the individual with internal support to succeed, even in difficult life situations, and is an important basis for social adaptation and emotional well-being.
Keywords: self-esteem; hardiness; personality; difficult life situation